Responsibilities of Land Deed Officers (PPAT) For Selling Buying Deed - Lisa Ayu Ningsih; Sriono Sriono; Elviana Sagala; Risdalina Risdalina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Sale and purchase are an agreement in which one party binds himself to surrender ownership of an item and the other party pays the promised price. The oﬃcial who has the authority to make and ratify an authentic deed of a right to be transferred is a notary. If an agreement does not meet the subjective requirements, then the agreement can be canceled. Meanwhile, if an agreement does not meet the objective requirements, then the agreement is null and void. The type of research in this article is normative juridical research where in this study the author only takes secondary data, namely library materials obtained by the author including oﬃcial documents, library books, laws and regulations, scientiﬁc works, articles, and documents. -documents related to research material. Secondary data collection throughlibrary researchis done by studying and collecting data related to the author's research. The Land Deed Making Oﬃcial (PPAT) is responsible for the validity of the registration requirements for the transfer of land rights. The Land Deed Making Oﬃcer (PPAT) is also responsible to the parties for making a land deed and managing it eﬀectively until it is completed. If there is a dispute in the Court, it is expected that the testimony of the parties, the Land Deed Oﬃcial (PPAT) is only asked to be responsible for providing evidence in the form of a letter that has been made by the PPAT.